Analisa Metode SHA-512 Untuk Tanda Tangan Digital Pada File Video - Mhd Ipdal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Cryptography is the science of maintaining data security. Cryptography is a data security method that can be used to maintain data authenticity, data confidentiality, and data transmission authenticity. SHA-512 is a one-way hash function designed by the National Security Agency (NSA) and published by the National Institute of Standards and Technology (NIST) as the Federal Information Processing Standard (FIPS) in 1993 and referred to as SHA-0, two years later. published next generation SHA 1 which is an improvement of the SHA-0 algorithm. In 2002 four other variations were published, namely SHA-224, SHA-256, SHA-384, and SHA-512, four of which were referred to as SHA-2. The SHA-512 hash function is a function that produces a message digest of 512 bits in size and 1024 bits in length. There are 80 loops in this function. This research will use the SHA-512 Method to secure the authenticity, confidentiality, integrity, and authentication of digital signatures on video files. This study describes the security process to detect the authenticity of digital signatures on video files using the SHA-512 method in the form of detecting digital signatures on confidential video files sent via public telecommunications that cannot be changed or modified by unauthorized persons or persons who not concerned. This is done as an effort to minimize fraudulent acts, forgery, hoaxes, or misuse of digital signatures on video files.